A Forecasting Study on Electricity Consumption in Indian Textile Industries: An Economic Analysis - T, Amose,; N, Sreedevi.; K.R, Jeyakumar (The journal of contemporary issues in business and government, 2021)
Electricity as an important input plays a vital role from each and every economic movements for the development of the country at global level. Textile industry is not differed from this context; it provides outputs to trade at International markets. In India, textile industry is one among the important industries which supports economic development and trade balance. Hence, supply and demand for electricity in Indian textile industries are the signified economic processes to attain maximum output. Hence, the study emphasised electricity consumption and its cost which effects from consumption per unit of electricity for the Indian textile industry. This study brought out secondary data collected from various published articles and reports. It covers 30 years of forecasted data collected from 2001 to 2030 (Estimated). And data have been analysed by statistical tools such as correlation and regression. Findings of the study has highlighted that there is close relationship within and between the dependent and independent variables. Finally, the study has been concluded with effective policy recommendations with an overview of study.